2004
DOI: 10.1007/s00299-004-0788-9
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for plant cell biology: in vivo antibody uptake in plant protoplasts

Abstract: We report on the in vivo uptake of antibodies into plant protoplasts. It is shown by immunofluorescence that when protoplasts of sunflower, Arabidopsis or tobacco were incubated in vivo with an antibody, this antibody was detected in the cytoplasm and/or the nucleus, depending on the location of the target protein. Furthermore, when protoplasts were cultured in the presence of antibodies specific effects were observed. Incubation with antibodies raised against p34 cdc2 led to a strong inhibition of the divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…"Blot ting" pro -ce dures (South ern, north ern and west ern) are routine to con firm gene in te gra tion and ex pres sion in trans gen ic plants (Har ding andMillam 2000, Bhat andSrinivasan 2002). Bričre et al (2004) have shown that an ti bod ies can pen e trate into liv ing plant proto plasts and, there fore, may be pow er ful tools in eval u at ing pro tein func tion.…”
Section: Mo Lec U Lar Anal Y Sis Of Novel Plants Gen Er Ated By In VImentioning
confidence: 99%
“…"Blot ting" pro -ce dures (South ern, north ern and west ern) are routine to con firm gene in te gra tion and ex pres sion in trans gen ic plants (Har ding andMillam 2000, Bhat andSrinivasan 2002). Bričre et al (2004) have shown that an ti bod ies can pen e trate into liv ing plant proto plasts and, there fore, may be pow er ful tools in eval u at ing pro tein func tion.…”
Section: Mo Lec U Lar Anal Y Sis Of Novel Plants Gen Er Ated By In VImentioning
confidence: 99%
“…Although semipermeable, plant primary cell walls only allow molecules and proteins up to 60-120 kDa in size to enter [9,10], making them impermeable to antibodies exceeding this size limit. Thus, to increase the access of antibody, cell walls can be enzymatically removed and the released protoplasts studied [11]. For live-cell imaging, the expression of biological fluorochromes has become a valuable and powerful alternative to immunofluorescence.…”
Section: Exogenous Fluorochrome Application In Living Plant Tissuesmentioning
confidence: 99%